Basic Components in Creating Contents for Mathematics Subject Using Digital Wayang Kulit: A Conceptual Model - Mohd Amran, Md Ali (2011)
This research intends to develop a conceptual model that illustrates how multimedia approaches could be used to enhance teaching and learning of a Mathematics subject in primary school as well as to preserve Wayang Kulit in younger generation. A prototype will be developed to demonstrate how the content of a standard one Mathematics subject in primary school could be transferred into multimedia form. The prototype is developed in a form of Digital Wayang Kulit to present the contents based on the syllabus of Mathematics education using the actors of Wayang Kulit.